2009
DOI: 10.1007/s00221-009-1932-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of receptor protein tyrosine phosphatases accompanies the reorganisation of the retina upon laser lesion

Abstract: The regulation of protein phosphorylation plays an essential role in virtually all aspects of eukaryotic development. Beginning with the regulation of the cell cycle to cellular proliferation and differentiation, the delicate balance between the phosphorylating activity of kinases and the dephosphorylation by phosphatases controls the outcome of many signal transduction cascades. The generation of cellular diversity occurs in an environment that is structured by the extracellular matrix (ECM) which forms a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In the adult retina, tenascin-C is expressed by amacrine and displaced amacrine cells as well as by horizontal cells [64]. In central nervous tissue a dynamic regulation of tenascin-C was additionally described in reactive astrocytes after lesions [65][66][67][68]. Based on these findings, we speculate that reactive astrocytes of the optic nerve and neuronal cells of the retina up-regulate tenascin-C following RGC death and axon degeneration.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the adult retina, tenascin-C is expressed by amacrine and displaced amacrine cells as well as by horizontal cells [64]. In central nervous tissue a dynamic regulation of tenascin-C was additionally described in reactive astrocytes after lesions [65][66][67][68]. Based on these findings, we speculate that reactive astrocytes of the optic nerve and neuronal cells of the retina up-regulate tenascin-C following RGC death and axon degeneration.…”
Section: Discussionmentioning
confidence: 65%
“…Another CSPG, neurocan, was found to be up‐regulated in the retina after transient ischaemia . Moreover, in a retinal laser lesion model phosphacan/RPTP β / ζ exhibits increased expression levels . It was shown that it promotes axonal regeneration and repair processes in the CNS .…”
Section: Discussionmentioning
confidence: 99%
“…Other extracellular interaction partners are TN-C, Contactin/F3/F11, the cell adhesion molecules L1CAM and NCAM (Klausmeyer et al, 2007), and FGF (Milev et al, 1998b). RPTPβ isoforms are regulated after knife lesion of the cerebral cortex (Dobbertin et al, 2003), striatal stab wound (Barker et al, 1996), and after retinal laser lesion (Besser et al, 2009) and are critical for recovery (Harroch et al, 2002). PSI as the smallest member of the RPTPβ family promotes axon growth (Garwood et al, 2003).…”
Section: Extracellular Signals Influence Regeneration and Stem/progenmentioning
confidence: 99%
“…Notably, elevated levels of the CSPGs aggrecan, brevican and phosphacan were noted in the optic nerve after retinal ischemia (Reinhard et al, 2017 ). Following laser lesion, differential expression of RPTPβ/ζ was observed in the retina (Besser et al, 2009 ). In the non-injured retina of Tnc deficient mice, an upregulation of the DSD-1 epitope, recognized by the monoclonal antibody 473HD and localized on phosphacan/RPTPβ/ζ, was revealed when compared to the wild-type mice (Besser et al, 2012 ).…”
Section: Tenascin Signaling and The Interacting Matrisome Under Pathomentioning
confidence: 99%